HAK SUBJEK DAN POTENSI PELANGGARAN HAK ASASI MANUSIA DALAM PENELITAN MEDIS - Dipo Pramudito; Gunawan Widjaja (Cross-border, 2022)
Due to development of civilization and human needs research is needed to produce new findings that are useful for mankind. Research in the field of health involving humans as the subject has a potential risk of violations of human rights and the integrity of human dignity. For example, BPOM's findings on clinical trials of Nusantara vaccines include ethical violations. The purpose of this study is to understand the potential for human rights violations in health research and how to anticipate human rights violations that may occur. This research is a normative juridical research with data sources from primary legal materials such as legislation, and secondary legal materials such as journals and books. This research is also multi-disciplinary in which medical science is involved in the discussion. The results of this study are the potential for disability or disease caused by research that is not in accordance with protocols and ethics, subject data is not maintained and so on. Meanwhile, to prevent violation, strict supervision and research development in layers by the authorities and institutions is required. The recommendation from this research is to provide a wider space for the authorized institution to oversee the implementation of research ethics in health research activities so that violations of the rights of research subjects can be minimized.